Nutritional optimization of fecal microbiota transplantation in humans: a scoping review - Levi M Teigen; Austin Hoeg; Hijab Zehra; Priyali Shah; Remy Johnson; Kristen Hutchison; Megan Kocher; Annie W Lin; Abigail J Johnson; Byron P Vaughn (Gut Microbes, 2025)
Diet constitutes a major source of nutrient flow to the gut microbes. As such, it can be used to help shape the gut microbiome. Fecal microbiota transplantation (FMT) is an increasingly promising therapy in disease states beyond recurrent Clostridioides difficile infection, but diet is largely overlooked for its potential to help optimize this therapy. Therefore, the aim of this scoping review is to present the literature landscape that captures pre- and post-FMT dietary intake in humans, identify research gaps, and provide recommendations for future research. A comprehensive search strategy was developed and searches were run in five databases. Studies were included if they discussed adults who underwent FMT for any recognized treatment indication and had dietary intake as a study objective, this search encompassed studies with interventions that included foods and dietary supplements. The initial screening identified a total of 7721 articles, of which 18 met the inclusion criteria for this review. Studies were heterogeneous, but taken together, they introduce a framework that defines important nutritional considerations for both donors and FMT recipients in the period around FMT dosing. This framework is summarized with this review and highlights the opportunities available to develop FMT-based precision nutrition strategies to optimize its clinical efficacy.